Termination Of Prosecution Based On Restorative Justice In Negligence Caused Death At The Purbalingga District Prosecutor - Dira, Gloria Rakhel Qamara (UMPurwokerto Law Review, 2022)
Abstract Sentencing can be interpreted as the stage of determining sanctions for perpetrators of crimes in criminal law. One method of imposing criminal sanctions is litigation or the courts. However, in practice, it doesn't always go as expected. This study aimed to determine the legal arrangements regarding the termination of prosecution based on Restorative Justice and its application. The research method used is normative juridical, namely through library research which examines mainly secondary data in the form of laws and regulations, books, other legal documents, research results, and other references. The results of this study are that through a Restorative Justice approach, it is hoped that recovery for victims can be realized, the purpose of punishment for perpetrators will be successful, and public order can be achieved. Restorative justice is one alternative to realizing justice under the objectives of the law. Justice will be obtained by all parties, both perpetrators, victims, and the community. Restorative justice provides the best solution by prioritizing an approach that focuses on recovery with participation between perpetrators, victims, and the community in resolving criminal cases. Keywords: Restorative Justice, Termination, Prosecution Abstrak Pemidanaan dapat diartikan sebagai tahapan penetapan sanksi kepada pelaku kejahatan di dalam hukum pidana. Salah satu metode penjatuhan sanksi pidana adalah menggunakan jalur litigasi atau melalui pengadilan. Namun, dalam praktiknya tidak selalu berjalan sesuai dengan apa yang diharapkan. Tujuan penelitian ini adalah mengetahui pengaturan hukum mengenai penghentian penuntutan berdasarkan Restorative Justice serta penerapannya. Metode penelitian yang digunakan adalah yuridis normatif yaitu melalui studi pustaka yang menelaah terutama data sekunder berupa peraturan perundang-undangan, buku, dokumen hukum lainnya, hasil penelitian, serta referensi lainnya. Hasil penelitian ini adalah melalui pendekatan Restorative Justice diharapkan pemulihan bagi korban dapat terealisasi, tujuan pemidanaan bagi pelaku akan berhasil dan ketertiban masyarakat pun dapat tercapai. Restorative Justice merupakan salah satu alternatif untuk mewujudkan keadilan sesuai dengan tujuan hukum. Keadilan yang akan diperoleh semua pihak, baik pelaku, korban maupun masyarakat. Restorative Justice memberikan solusi terbaik dengan mengedepankan suatu pendekatan yang menitikberatkan pada pemulihan dengan partisipasi antara pelaku, korban, dan masyarakat dalam proses penyelesaian perkara pidana. Kata Kunci : Restorative Justice, Penghentian, Penuntutan.